Serum Angiotensin-Converting Enzyme as a Non-Invasive Biomarker for Identifying Vulnerable Coronary Plaques by Coronary CT Angiography in Patients Presenting with Chronic Coronary Syndrome (University Heart Journal, 2026)
Cardiovascular disease (CVD) remains the leading cause of premature death worldwide, accounting for approximately 20.5 million deaths annually. Chronic coronary syndrome (CCS) is characterized by a chronic mismatch between myocardial oxygen supply and demand, most commonly resulting from atherosclerotic coronary obstruction. Vulnerable coronary plaques, defined by high-risk morphological features on coronary computed tomography angiography (CCTA), are major precursors of acute coronary events. Angiotensin-converting enzyme (ACE), a key component of the renin–angiotensin system, is abundantly expressed in atherosclerotic lesions and macrophages; however, its clinical utility as a serum biomarker for coronary plaque vulnerability has not been previously investigated.Aim of the Study: To evaluate serum ACE as a non-invasive biomarker for identifying vulnerable coronary plaques in patients with chronic coronary syndrome using CCTA as the reference standard.Methods: This cross-sectional study enrolled 30 consecutive adult patients with CCS who underwent CCTA at Bangladesh Medical University (BMU) and Ibrahim Cardiac Hospital & Research Institute, Dhaka, Bangladesh (August 2023–September 2025). Plaque morphology was assessed on a 128-slice SIEMENS SOMATOM CT scanner with ECG-gating. Vulnerable plaque was defined by the presence of at least one high-risk CCTA feature: low-attenuation plaque, positive remodeling, spotty/micro calcification, or napkin-ring sign. Serum ACE activity was measured within 48 hours of CCTA using the kinetic FAPGG hydrolysis method on a Siemens Atelica Solution analyzer. Participants were equally divided into vulnerable-plaque (n=15) and non-vulnerable-plaque (n=15) groups. Diagnostic performance was assessed by receiver operating characteristic (ROC) curve analysis.Results: Among 30 patients with chronic coronary syndrome, 15 had vulnerable coronary plaques and 15 had non-vulnerable plaques on CCTA. Baseline demographic and cardiovascular risk factors were comparable between the groups, with no statistically significant differences observed (all p>0.05). Serum ACE levels were significantly higher in patients with vulnerable plaques compared with those with non-vulnerable plaques (40.02±21.54 vs. 12.56±7.27 U/L, p